The Impact of Bait Ball and Hanging Ball Training on Smash Ability in Volleyball Games - Amir Supriadi; Budi Valianto; Nurkadri Nurkadri (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
This study aims to determine the effect of the bait ball and hang ball smash training on the smash ability of male athletes. The method used in this study was an experimental method and the subjects of this study consisted of 12 athletes. Data collection was carried out in two stages, namely: pre-test and post-test which were data collected after carrying out a training program. After the data was collected, an analysis was carried out: Hypothesis I. A t-count of 8.62 was obtained. then this price is compared with the ttable price with dk = n – 1 (6-1 = 5) at a significant level a = 0.05 is 2.75 thus t-count > t-table (8.62 > 2.75). This means that Ho is rejected and Ha is accepted. Thus it can be concluded that there is a significant influence from the form of bait ball smash training. Hypothesis II. Obtained a t-count of 3.85. then this price is compared with the ttable price with dk = n – 1 (6-1 = 5) at a significant level a = 0.05 is 2.75 thus t-count > -ttable (3.85 > 2.75). This means that Ho is rejected and Ha is accepted. Thus it can be concluded that there is a significant influence from the form of hanging ball smash training. Hypothesis III. Obtained a t-count of 0.39. then this price is compared with the ttable price with dk = n1 + n2 – 2 = 10) at a significant level a = 0.05 is 2.23, thus t-count < t-table (0.39 > 2.23). This means that Ho is accepted and Ha is rejected. Thus it can be concluded that the form of bait ball smash training has no greater effect than the hanging ball smash practice on the results of smashes in male athletes.